2001
DOI: 10.1037/1064-1297.9.2.163
|View full text |Cite
|
Sign up to set email alerts
|

Dose–response effects of methylphenidate on ecologically valid measures of academic performance and classroom behavior in adolescents with ADHD.

Abstract: The effects of methylphenidate on the academic performance and classroom behavior of 45 adolescents with attention deficit hyperactivity disorder were studied. During a 6-week, placebo-controlled medication assessment in the context of a summer treatment program, participants received a double-blind, crossover trial of 3 doses of methylphenidate. Dependent measures included note-taking quality, quiz and worksheet scores, written language usage and productivity, teacher ratings, on-task and disruptive behavior,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
91
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 155 publications
(106 citation statements)
references
References 31 publications
11
91
3
Order By: Relevance
“…Teacher ratings of attention problems in early childhood have been implicated in low math and reading achievement in late adolescence, even after adjusting for childhood IQ and family factors (Breslau 2009). Stimulant treatment has been associated with improved scores in reading in a large, population-based study (Barbaresi et al 2007) and with improved written language usage, note-taking quality, homework completion, and accuracy on reading and math tasks (Elia et al 1993;Evans et al 2001;Vance et al 2003). Although some of these measures failed to reach statistical significance in the predetermined sequence specified for the statistical analysis, this study demonstrated positive effects of OROS MPH compared with placebo in some domains noted to be critical to academic progress.…”
Section: Discussionmentioning
confidence: 69%
“…Teacher ratings of attention problems in early childhood have been implicated in low math and reading achievement in late adolescence, even after adjusting for childhood IQ and family factors (Breslau 2009). Stimulant treatment has been associated with improved scores in reading in a large, population-based study (Barbaresi et al 2007) and with improved written language usage, note-taking quality, homework completion, and accuracy on reading and math tasks (Elia et al 1993;Evans et al 2001;Vance et al 2003). Although some of these measures failed to reach statistical significance in the predetermined sequence specified for the statistical analysis, this study demonstrated positive effects of OROS MPH compared with placebo in some domains noted to be critical to academic progress.…”
Section: Discussionmentioning
confidence: 69%
“…Because many of these difficulties worsen in middle and junior high schools, once-a-day dosing would seem to have particular usefulness in this population. IR MPH tid has a clearly beneficial effect on young adolescents on measures analogous to those we used in this study, 66,67 although such studies have not yet been performed with Concerta. In this study, children took (placebo) pills 3 times a day, including lunchtime and after-school doses.…”
Section: Discussionmentioning
confidence: 91%
“…20,70 Such findings on objective indices of work performance no doubt give rise to teacher ratings of improved task completion. Unfortunately, these acute effects, despite the fact that they continue in adolescence, 66 have not yet been shown to translate into long-term gains in academic achievement, even with long-term stimulant use. 25 A third point relevant to the extant literature concerns our measures of peer interactions in recreational settings.…”
Section: Discussionmentioning
confidence: 99%
“…The child's academic achievement was assessed using the dictation subtest (Woodcock, 1977). This subtest was used because written language tasks are often difficult for children with ADHD (e.g., Evans et al, 2001). …”
Section: Dishion Measure Of Peer Relationshipsmentioning
confidence: 99%